MOTIVATION, AND LEADERSHIP ON THE PERFORMANCE OF CHILD FRIENDLY INTEGRATED PUBLIC SPACE MANAGERS - Riyanto Wujarso; Muhammad Fachri Ramadhan; Sita Dewi; Revan Andhitiyara; Adrian Adrian (JISAMAR (Journal of Information System, Applied, Management, Accounting and Research), 2023)
The purpose of this study is to investigate how factors such as work culture, work motivation, and leadership influence the performance of managers working for Child-Friendly Integrated Public Spaces (RPTRA) in Jakarta in the year 2022. This research utilized a survey approach along with a technique known as purposive sampling. The managers of RPTRA in Jakarta made up the total of 75 participants that participated in the research. The data were examined with the assistance of the SPSS software package using a multiple linear regression analysis. The findings revealed that both the work culture and the leadership style of RPTRA managers in Central Jakarta in 2022 had a substantial impact on the performance of those managers. In the meantime, research shows that the level of job motivation of RPTRA managers in Jakarta in 2022 has no meaningful effect on their performance. In the same way, the performance of RPTRA managers is impacted by these three aspects simultaneously. It is possible to draw the following conclusion based on the findings of this study: RPTRA managers in Central Jakarta need to improve both their work culture and their work motivation in order to enhance their performance in managing child-friendly RPTRAs.